Location dependence of the transcriptional response of a potential G-quadruplex in gene promoters under oxidative stress - Fleming, Aaron M (Nucleic Acids Res, 2019)
Oxidation of the guanine (G) heterocycle to 8-oxo-7,8-dihydroguanine (OG) in mammalian gene promoters was demonstrated to induce transcription. Potential G-quadruplex forming sequences (PQSs) in promoters have a high density of G nucleotides rendering them highly susceptible to oxidation and possible gene activation. The VEGF PQS with OG or an abasic site were synthesized at key locations in the SV40 or HSV-TK model promoters to determine the location dependency in the gene expression profile in human cells. The PQS location with respect to the transcription start site (TSS) and strand of occupancy (coding versus non-coding strand) are key parameters that determine the magnitude and direction in which gene expression changes with the chemically modified VEGF PQS. The greatest impact observed for OG or F in the PQS context in these promoters was within ∼200 bp of the TSS. Established PQSs found to occur naturally in a similar location relative to the TSS for possible oxidation-induced gene activation include c-MYC, KRAS, c-KIT, HIF-1α, PDGF-A and hTERT. The studies provide experimental constraints that were used to probe bioinformatic data regarding PQSs in the human genome for those that have the possibility to be redox switches for gene regulation.